Size matters: the Juniperus deppeana Steud. (sabino) big fruits are more sensitive to insect depredation - Martínez, Armando J.; Sainos, Pilar; Lezama Delgado, Ernesto; Angeles-Álvarez, Guillermo (Instituto de Ecología, A.C., 2016)
The relationship between fruit size of Juniperus deppeana and damage caused by seed predator insects, in a forest fragment of Juniperus deppeana ( sabino), typical of the state of Tlaxcala, Mexico was analyzed. Female trees were selected to quantify fruit maturation. Their availability were classified into three categories: small (5 to 9 mm), medium (10-12 mm), and large (13 to 15 mm). At the same time, the amount and density of intact fruits and those presenting insect damage were quantified on five different samplings. Between 21-46 of the individuals presented fruits in 50 to 70% of the tree (by visual estimation). Also, categories of 5 to 30% of galbule abundance in the crowns were presented in 19 to 31 of the female individuals during the five different dates when the per cent quantifications were made. Female individuals produced fruits continuously from august 2004 to august 2005 . Although there was always a wide availability of large, medium, and small fruits, the first ones were the most damaged, since up to 30% of the fruits in that category presented exit holes caused by seedpredator insects.